Identify Indonesian Psychology Publications in PsycINFO Database: A Scoping Review - Indra Yohanes Kiling; Beatriks Novianti Bunga (ANIMA Indonesian Psychological Journal, 2015)
Psychology field in Indonesia has grown for years and its publications have spread in various academic media. The aim of this study was to locate existing literature in a database with solid reputation to give insight about the current progress of psychology in Indonesia. A literature search of PsycINFO database was performed. There were no date or language restrictions. Narrative analysis was used to synthesize findings. Seventy articles were identified from the search terms and four articles were considered relevant. Three of the four relevant studies were focused in the subfield of cross-cultural psychology. Some patterns of publishing in both relevant and irrelevant articles were found and discussed. This study is considered among the first scoping study that has been done in Indonesian context.